Hydrophilic and superoleophobic ceramic membrane as well as preparation method and application thereof

By forming a complete α-Fe2O3 film layer on the surface of the microporous ceramic membrane, the problems of low membrane flux and poor anti-pollution effect in the separation of oil-containing wastewater are solved, and high throughput and excellent oil-water separation performance are achieved.

CN120361738AActive Publication Date: 2025-07-25QINGYUAN INNOVATION LABORATORY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510513499.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-23
Publication Date
2025-07-25
Estimated Expiration
2045-04-23

AI Technical Summary

Technical Problem

The existing ceramic membrane has poor membrane anti-pollution effect, low membrane flux and poor oil-water separation effect during the oil-water separation process of oil-containing wastewater.

Method used

A complete α-Fe2O3 film layer is formed on the surface of the microporous ceramic membrane. By regulating the particle size and viscosity of the iron hydroxide sol and combining with the use of polyvinyl alcohol, a high-throughput hydrophilic and superoleophobic ceramic membrane is prepared.

Benefits of technology

It significantly improves the permeability and oil-water separation effect of the membrane, enhances the film's anti-pollution ability and operating stability, and reduces the degree of scaling on the membrane surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120361738A_ABST
    Figure CN120361738A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrophilic and superoleophobic ceramic membrane and a preparation method and application thereof, and belongs to the technical field of ceramic membranes, the hydrophilic and superoleophobic ceramic membrane comprises a supporting layer, a transition layer loaded on the surface of the supporting layer and an iron oxide membrane layer loaded on the surface of the transition layer, and the average pore size of the iron oxide membrane layer is 2-100 nm. The viscosity and the particle size of the Fe (OH) 3 sol membrane preparation liquid are regulated and controlled to be matched with the pore diameter of a transition layer on the surface of the microporous ceramic membrane, and a new complete iron oxide separation layer is formed on the surface of the microporous ceramic membrane. The membrane flux and the flux recovery rate of the hydrophilic and superoleophobic ceramic membrane in an oil-water separation system are far superior to those of an original microporous ceramic membrane, and the hydrophilic and superoleophobic ceramic membrane has the advantages of membrane pollution resistance, high membrane flux and high oil-water separation efficiency when being applied to the oil-water separation process of a high-concentration oil-water system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic membranes, and particularly relates to a hydrophilic and super-oleophobic ceramic membrane, a preparation method thereof, and an application thereof. Background Art

[0002] Oily wastewater exists in almost every industry, and most of the oily wastewater in the world is generated during the oil and gas extraction process. In order to treat oily wastewater, various treatment technologies have been developed. However, traditional separation technologies have many drawbacks.

[0003] In recent years, membrane technology is a new type of water treatment technology and is considered to be one of the most promising methods for treating oily wastewater. Ceramic membranes in membrane technology have been widely used in harsh environments such as the petroleum and chemical industries due to their good chemical stability, high mechanical strength, acid and alkali resistance, high temperature resistance and other advantages. Generally speaking, a smooth membrane surface is beneficial to reducing fouling. Fe2O3 is considered a natural hydrophilic material with rich sources and low prices. Due to the high hydrophilicity of nano iron oxide particles, the Fe2O3 nanoparticles deposited on the membrane surface result in the least fouling tendency.Patent CN 113926321A obtained an anti-pollution ceramic membrane by modifying the surface of a ceramic microfiltration membrane with Fe2O3. However, this patent clearly states that only Fe2O3 was modified on the surface of the ceramic microfiltration membrane. The particle size of the iron hydroxide sol prepared in Example 2 of this patent was only 40-50 nm. Under these conditions, it was impossible and did not form a complete iron oxide film layer on the surface of the ceramic support with a pore size of 100 nm. Therefore, this patent also has no corresponding data support such as the pore size of the iron oxide film layer. Similarly, Barati N et al. (Barati N, Husein M M, Azaiez J. Modifying ceramic membranes with in situ grown iron oxide nanoparticles and their use for oily water treatment[J]. Journal of Membrane Science, 2020, 617:118641.) and Karnik B S et al. (Karnik B S, Baumann M J, Masten S J, et al. AFM and SEM characterization of iron oxide coated ceramic membranes[J]. Journal of Materials Science, 2006, 41(20):6861-6870.) also modified iron oxide nanoparticles on the surface of the ceramic membrane. However, no complete iron oxide film layer was formed on the surface of the ceramic membranes disclosed in these literatures (Barati N et al. directly stated in the 8th and 9th lines of the 4th paragraph in Section 3.1.2 of their literature that the formation of an additional layer composed only of nano-iron oxide was not observed; Karnik B S et al. showed the EDS energy spectrum of the iron oxide-coated ceramic membrane prepared according to the method in the literature (Fig. 9b) in their literature. It can be clearly seen from the figure that the surface of the modified ceramic membrane was mixed with chemical substances of different sizes and morphologies (titanium dioxide, zirconium oxide, iron oxide, and aluminum oxide), and the signal response of the EDS energy spectrum of the Fe element was uneven, indicating that only the surface of the ceramic membrane was modified with iron oxide. If a complete film layer was formed, the surface of the modified ceramic membrane should be composed of chemical substances of uniform size and similar morphology, iron oxide, and the signal response of the Fe element in the EDS energy spectrum of the Fe element should be uniform).

[0004] The traditional method for preparing an iron oxide film is to coat a suspension of iron oxide particles with a particle size of a few nanometers on a ultrafiltration membrane with a small pore size. According to the Hagen-Poiseuille equation, the flux of the ultrafiltration membrane with a small pore size will not be too high. The low membrane flux limits the oil-water separation ability of the ceramic membrane for oily wastewater. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a hydrophilic and superoleophobic ceramic membrane, its preparation method and application, aiming at the problems of poor anti-fouling effect, low membrane flux and poor oil-water separation effect of the ceramic membrane prepared by the prior art in the oil-water separation process of oily wastewater. A complete high-flux iron oxide membrane is prepared on a microfiltration membrane. The high-flux hydrophilic and superoleophobic ceramic membrane is promising for the separation of oil-water systems. Improving the sol process and regulating the particle size of iron hydroxide sol to prepare a high-flux iron oxide ceramic ultrafiltration membrane on a large-pore microfiltration membrane is a meaningful design scheme.

[0006] In order to achieve the above object, the technical solution provided by the present invention is as follows:

[0007] A hydrophilic and superoleophobic ceramic membrane, with a complete α-Fe2O3 membrane layer formed on the surface of a microporous ceramic membrane; for the α-Fe2O3 membrane layer, its average pore diameter is 2-100 nm, the porosity is 35-40%, and the membrane thickness is 1-2 microns.

[0008] Among them, the microporous ceramic membrane includes a support body and a transition layer loaded on the surface of the support body. The materials of the support body and the transition layer are independently selected from any one or several combinations of alumina, zirconia, magnesia, silica, titania, ceria, yttria, barium titanate, cordierite, mullite, forsterite, steatite, silicon aluminum oxynitride ceramic, zircon, ferrite, silicon nitride, aluminum nitride, silicon carbide, hydroxyapatite, carbon, silicon, clay, clay minerals, ceramic waste, silica sand, ceramic stone, feldspar and white sand.

[0009] Among them, the average pore diameter of the transition layer is 0.1-1 μm, preferably 100-300 nm.

[0010] The present invention also discloses a preparation method of the hydrophilic and superoleophobic ceramic membrane, including the following steps:

[0011] Step 1, an aqueous ferric chloride solution undergoes a high-temperature hydrolysis reaction to obtain an iron hydroxide sol, which is cooled to 70-90 °C, and polyvinyl alcohol (PVA) is added to the iron hydroxide sol to obtain an iron hydroxide sol film-forming solution; among them, the polyvinyl alcohol is polyvinyl alcohol type 124; the content of polyvinyl alcohol in the iron hydroxide sol film-forming solution is 0.05-2.5 wt%, and the solid content of iron hydroxide is 0.1-0.6 wt%.

[0012] Step 2, the microporous ceramic membrane is immersed in the iron hydroxide sol film-forming solution obtained in Step 1 for 1-60 s and then taken out, dried, and calcined to obtain the product.

[0013] In Step 1, the aqueous ferric chloride solution is any one of anhydrous FeCl3, FeCl3·6H2O, 2FeCl3·7H2O, and 2FeCl3·5H2O; the high-temperature hydrolysis reaction is as follows: dropping the aqueous ferric chloride solution into boiling water and reacting for 0.1 to 12 h under the condition of a temperature of 90 to 100 °C.

[0014] In Step 1, after adding an aqueous solution of polyvinyl alcohol to the iron hydroxide sol, reacting for 10 to 30 min under stirring and a temperature of 70 to 90 °C to obtain the film-forming solution of the iron hydroxide sol.

[0015] In Step 1, the particle size of the iron hydroxide colloid in the film-forming solution of the iron hydroxide sol is 100 to 200 nm.

[0016] In Step 2, the microporous ceramic membrane is a microporous ceramic membrane comprising the support layer and the transition layer, and the microporous ceramic membrane can be purchased on the market.

[0017] In Step 2, the drying temperature is 25 to 110 °C, the drying time is 1 to 48 h, preferably 12 h; the calcination temperature is 450 to 1000 °C, the calcination time is 1 to 24 h, preferably calcining at 700 °C for 2 h.

[0018] The present invention also discloses the application of the hydrophilic and superoleophobic ceramic membrane in the oil-water separation of an oil-water mixed system.

[0019] Among them, the oil-water mixed system is a mixed system of emulsified oil and water. The emulsified oil is tiny oil particles existing in a stable state (not floating, not aggregating), and the oil includes but is not limited to vegetable oil, industrial cutting oil, mineral oil, and artificial chemical synthesis oil (such as lubricating oil, silicone oil, etc.).

[0020] When using the hydrophilic and superoleophobic ceramic membrane for oil-water separation, the membrane surface flow rate is 1 to 4 m·s -1 , the transmembrane pressure difference is 1 to 3 bar, and the temperature is 20 to 60 °C.

[0021] Beneficial effects:

[0022] (1) In the present invention, the hydrated particle size and viscosity of the iron hydroxide sol are regulated by polyvinyl alcohol, the iron hydroxide sol is coated on the surface of the microporous ceramic membrane, and by matching the structure-activity relationship between the particle size of the iron hydroxide sol and the pore size of the transition layer on the surface of the microfiltration membrane, a new and complete iron oxide separation layer is formed on the surface of the microporous ceramic membrane, strengthening the oleophobic performance of the membrane surface and reducing the fouling degree on the membrane surface.

[0023] (2) The hydrophilic and super-oleophobic ceramic membrane surface of the present invention is formed by a complete iron oxide film layer composed of iron oxide nanoparticles, which significantly reduces the isoelectric point of the membrane surface. Due to the existence of electrostatic repulsion, the fouling degree of the iron oxide film in the oil-water system is significantly reduced, the permeation flux is significantly improved, and the oil-water separation effect is excellent.

[0024] (3) By drying and calcining the ceramic membrane coated with iron hydroxide sol, the present invention improves the bonding strength of iron oxide nanoparticles on the ceramic membrane surface and enhances the operation stability. Description of the Drawings

[0025] The following further specifically describes the present invention in conjunction with the drawings and specific embodiments, and the above and / or other advantages of the present invention will become clearer.

[0026] Figure 1 FIG. is the scanning electron microscope images of the surface and cross-section of the original alumina ceramic membrane and the ceramic membranes prepared in Example 1, Comparative Example 1, and Comparative Example 2; wherein, FIG. a is the scanning electron microscope image of the surface (left figure) and cross-section (right figure) of the original alumina ceramic membrane; FIG. b is the scanning electron microscope image of the surface (left figure) and cross-section (right figure) of the ceramic membrane prepared in Comparative Example 1; FIG. c is the scanning electron microscope image of the surface (left figure) and cross-section (right figure) of the ceramic membrane prepared in Comparative Example 2; FIG. d is the scanning electron microscope image of the surface (left figure) and cross-section (right figure) of the ceramic membrane prepared in Example 1.

[0027] Figure 2 FIG. is the element distribution map and EDS spectrum obtained by EDS scanning of the surface of the ceramic membrane prepared in Example 1; wherein, FIG. a is the Fe element distribution map of the ceramic membrane surface; FIG. b is the Al element distribution map of the ceramic membrane surface; FIG. c is the EDS spectrum obtained by energy spectrum scanning of the ceramic membrane surface.

[0028] Figure 3 FIG. is the underwater oil contact angle images of the surfaces of the original alumina ceramic membrane and the ceramic membrane prepared in Example 1; wherein, FIG. a is the underwater oil contact angle image of the surface of the original alumina ceramic membrane; FIG. b is the underwater oil contact angle image of the surface of the ceramic membrane prepared in Example 1.

[0029] Figure 4 FIG. is the underwater oil adhesion force images of the surfaces of the original alumina ceramic membrane and the ceramic membrane prepared in Example 1; wherein, FIG. a is the underwater oil adhesion force image of the surface of the original alumina ceramic membrane; FIG. b is the underwater oil adhesion force image of the surface of the ceramic membrane prepared in Example 1.

[0030] Figure 5 FIG. is the statistical chart of the leaching amount of Fe 3+ after the ceramic membrane prepared in Example 1 is immersed in water with pH values of 1, 3, and 5.

[0031] Figure 6Statistical chart of the Zeta potential on the surface of the original alumina ceramic membrane and the ceramic membrane prepared in Example 1 under different pH conditions in Example 3.

[0032] Figure 7 Statistical chart of the membrane flux during the oil-water separation process of the original alumina ceramic membrane and the ceramic membrane prepared in Example 1 in Example 4.

[0033] Figure 8 Statistical chart of the membrane flux recovery rate after the oil-water separation of the original alumina ceramic membrane and the ceramic membrane prepared in Example 1 in Example 4.

[0034] Figure 9 Process flow chart for the extraction of 9α-hydroxyandrostenedione in Example 5. Detailed implementation manners

[0035] The present invention will be further described according to the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and not to limit the present invention.

[0036] For specific technologies or conditions not specified in the embodiments, they shall be in accordance with the technologies or conditions described in the literature in this field or in accordance with the product specifications. For reagents or instruments whose manufacturers are not specified, they are all conventional products that can be obtained through regular channels.

[0037] Example 1

[0038] Accurately weigh 1.29 g of FeCl3·6H2O compound and add it to 50 mL of deionized water, ultrasonically dissolve it for 5 min, then dropwise add it to 40 mL of pre-boiled deionized water, heat it in an oil bath to 100 °C, keep the reaction going for 3 h, and then cool it to 80 °C to obtain iron hydroxide sol. Then, take 10 mL of 10 wt% PVA (type 124) aqueous solution and dropwise add it to the iron hydroxide sol, keep the reaction at 80 °C for 20 min, and finally cool it naturally to room temperature to obtain an iron hydroxide sol membrane-forming solution with a solid content of 0.5%. Mix it in a mixing-degassing machine for 3 min and degas it for 5 min, repeat the mixing and degassing 3 times, and measure the particle size of the iron hydroxide colloid to be 100 - 200 nm. Wash a flat alumina ceramic membrane with an average pore size of 100 nm (purchased from Nanjing Membrane Materials Industry Technology Research Institute Co., Ltd., with a diameter of 3 cm and a membrane thickness of 2 mm) clean with deionized water and dry it in an oven at 110 °C for 4 h. Immerse the cleaned alumina ceramic membrane in the iron hydroxide sol membrane-forming solution for 1 min, then take it out at a speed of 10 mm / s, air-dry it naturally, and then put it into a constant temperature and humidity oven at 70 °C and 110 °C for 24 h respectively, and then calcine it at 700 °C in a tubular furnace for 2 hours to obtain the hydrophilic and superoleophobic ceramic membrane of the present invention.

[0039] The microtopographies of the original alumina ceramic membrane and the hydrophilic and superoleophobic ceramic membrane prepared in this example were analyzed using a scanning electron microscope (SEM). The results are as Figure 1 shown in Figure a (chip-type alumina ceramic membrane) and Figure d (hydrophilic and superoleophobic ceramic membrane prepared in this example). By comparing the microtopographies of the ceramic membrane surface before and after coating the membrane-forming solution, it was found that compared with the original alumina ceramic membrane, a new α-Fe2O3 film layer with a thickness of 1.2 μm was formed on the surface of the hydrophilic and superoleophobic ceramic membrane, and the nanoparticles on its surface were smaller and the surface was smoother and flatter. The pore size of the α-Fe2O3 film layer in the hydrophilic and superoleophobic ceramic membrane prepared in this example was 103.1 nm, and the porosity was 36.9%.

[0040] The surface EDS energy spectrum analysis was carried out on the original alumina ceramic membrane and the hydrophilic and superoleophobic ceramic membrane prepared in this example. The results are as Figure 2 shown. By comparing the elements on the surfaces of the original alumina ceramic membrane and the hydrophilic and superoleophobic ceramic membrane prepared in this example, it was found that since the surface of the hydrophilic and superoleophobic ceramic membrane is a new iron oxide film layer, there is an obvious Fe element signal response on its surface, and the proportion of Fe element is 45.7 wt%.

[0041] Comparative Example 1

[0042] Accurately weigh 1.29 g of FeCl3·6H2O compound and add it to 50 mL of deionized water, ultrasonically dissolve it for 5 min, then dropwise add it to 40 mL of pre-boiled deionized water, heat it in an oil bath to 100 °C, keep the reaction going for 3 h, and then cool it to 80 °C to obtain iron hydroxide sol. Then, take 10 mL of 10 wt% PVA (type 2488) solution and dropwise add it to the iron hydroxide sol, keep the reaction at 80 °C for 20 min, and finally naturally cool it to room temperature to obtain an iron hydroxide sol membrane-forming solution with a solid content of 0.5%. Mix it in a mixing and degassing machine for 3 min and degas it for 5 min, repeat the mixing and degassing 3 times, and measure the particle size of the iron hydroxide colloid to be 350 - 450 nm. Clean a chip-type alumina ceramic membrane with an average pore size of 100 nm (purchased from Nanjing Membrane Materials Industry Technology Research Institute Co., Ltd., with a diameter of 3 cm and a membrane thickness of 2 mm) with deionized water and dry it in an oven at 110 °C for 4 h. Immerse the cleaned alumina ceramic membrane in the iron hydroxide sol membrane-forming solution for 1 min, then take it out at a speed of 10 mm / s, air-dry it naturally, and then place it in a constant temperature and humidity oven at 70 °C and 110 °C for 24 h, and then calcine it at 700 °C in a tubular furnace for 2 hours to obtain an iron oxide-modified ceramic membrane.

[0043] The microtopography of the iron oxide-modified ceramic membrane prepared in this comparative example was analyzed by SEM. The results are as Figure 1 shown in Figure b. By comparing the original alumina ceramic membrane ( Figure 1a), there is no obvious change in the surface micro-morphology of the iron oxide modified ceramic membrane prepared in this comparative example.

[0044] Comparative Example 2

[0045] Accurately weigh 1.29 g of FeCl3·6H2O compound and add it to 50 mL of deionized water. Ultrasonically dissolve it for 5 min, then dropwise add it to 40 mL of pre-boiled deionized water and heat it in an oil bath to 100 °C. After the reaction continues for 3 h, cool it down to 80 °C to obtain iron hydroxide sol. Then, take 10 mL of 10 wt% PVA (type 1788) solution and dropwise add it to the iron hydroxide sol. React at 80 °C for 20 min, and finally cool it naturally to room temperature to obtain an iron hydroxide sol membrane-forming solution with a solid content of 0.5%. Mix it in a mixing-degassing machine for 3 min and degas for 5 min. Repeat the mixing and degassing 3 times. Measure the particle size of the iron hydroxide colloid to be 230 - 340 nm. Clean a plate-type alumina ceramic membrane with an average pore size of 100 nm (purchased from Nanjing Membrane Materials Industry Technology Research Institute Co., Ltd., with a diameter of 3 cm and a membrane thickness of 2 mm) with deionized water and dry it at 110 °C for 4 h. Immerse the cleaned alumina ceramic membrane in the iron hydroxide sol membrane-forming solution for 1 min, then take it out at a speed of 10 mm / s, air-dry it naturally, and then place it in a constant temperature and humidity oven at 70 °C and 110 °C for 24 h, and then calcine it at 700 °C in a tube furnace for 2 h to obtain the iron oxide modified ceramic membrane.

[0046] Analyze the micro-morphology of the iron oxide modified ceramic membrane prepared in this comparative example by SEM. The results are as Figure 1 shown in Figure c. Compare with the original alumina ceramic membrane ( Figure 1 a), an iron oxide layer appears on the surface of the iron oxide modified ceramic membrane prepared in this comparative example, but it is not complete.

[0047] Example 2

[0048] Accurately weigh 1.29 g of the compound FeCl3·6H2O and add it to 50 mL of deionized water. Ultrasonically dissolve it for 5 min. Then, dropwise add it to 40 mL of pre-boiled deionized water and heat it in an oil bath to 100 °C. After reacting for 3 h, cool it down to 80 °C to obtain iron hydroxide sol. Next, take 10 mL of a 10 wt% PVA (type 124) aqueous solution and dropwise add it to the iron hydroxide sol. React at 80 °C for 20 min. Finally, naturally cool it to room temperature to obtain an iron hydroxide sol film-forming solution with a solid content of 0.5%. Mix it in a mixing-degassing machine for 3 min and degas for 5 min. Repeat the mixing and degassing 3 times. Measure the particle size of the iron hydroxide colloid in it to be 100 - 200 nm. Clean a plate-type alumina ceramic membrane with an average pore size of 200 nm (purchased from Nanjing Membrane Materials Industry Technology Research Institute Co., Ltd., with a diameter of 3 cm and a membrane thickness of 2 mm) with deionized water and dry it at 110 °C for 4 h. Immerse the cleaned alumina ceramic membrane in the iron hydroxide sol film-forming solution for 1 min, then take it out at a speed of 10 mm / s, and naturally dry it. Then, put it into a constant temperature and humidity oven at 70 °C and 110 °C for 24 h, and then calcine it at 700 °C in a tube furnace for 2 h to obtain the hydrophilic and super-oleophobic ceramic membrane of the present invention.

[0049] In the hydrophilic and super-oleophobic ceramic membrane prepared in this example, the thickness of the α-Fe2O3 film layer is 2 μm, the pore size is 130.6 nm, and the porosity is 38%.

[0050] Example 3

[0051] Perform an underwater oleophobic property analysis on the original alumina ceramic membrane and the hydrophilic and super-oleophobic ceramic membrane prepared in Example 1. The results are as Figure 3 shown. Compared with the underwater oil contact angle on the surface of the original alumina ceramic membrane, due to the formation of a new iron oxide film layer on the surface of the hydrophilic and super-oleophobic ceramic membrane, its underwater oil contact angle increases from 155° of the original alumina ceramic membrane to 162°, and the resistance of the membrane surface to oil droplet wetting performance is enhanced.

[0052] Measure the underwater oil adhesion force on the surface of the original alumina ceramic membrane and the hydrophilic and super-oleophobic ceramic membrane prepared in Example 1. The results are as Figure 4 shown. Compared with the underwater oil adhesion force on the surface of the original alumina ceramic membrane, due to the formation of a new iron oxide film layer on the surface of the hydrophilic and super-oleophobic ceramic membrane, its underwater oil adhesion force decreases from 0.159 mN of the original alumina ceramic membrane to 0.075 mN, a decrease of 52.8%. The resistance of the membrane surface to oil droplet adhesion performance is significantly enhanced, indicating that the hydrophilic and super-oleophobic ceramic membrane prepared by the present invention has excellent anti-membrane fouling performance and oil-water separation performance.

[0053] The hydrophilic and superoleophobic ceramic membrane prepared in Example 1 was analyzed for chemical stability by soaking it in water with pH values of 1, 3, and 5 for 1 day, 7 days, and 14 days, and measuring the Fe 3+ content (i.e., the Fe 3+ leaching amount) in water under different conditions. The results are as Figure 5 shown. The Fe 3+ leaching amount of the hydrophilic and superoleophobic ceramic membrane prepared in Example 1 was the largest after soaking in water with pH = 1, which was 0.3 - 0.35 mg / L. Under weakly acidic and neutral conditions, no Fe 3+ was leached, indicating that the hydrophilic and superoleophobic ceramic membrane of the present invention has excellent chemical stability.

[0054] Zeta potential analysis was performed on the surfaces of the original alumina ceramic membrane and the hydrophilic and superoleophobic ceramic membrane prepared in Example 1. The results are as Figure 6 shown. Compared with the isoelectric point pH = 9 of the surface of the original alumina ceramic membrane, the isoelectric point of the surface of the hydrophilic and superoleophobic ceramic membrane prepared in Example 1 decreased to pH = 5.7. Under neutral conditions, the Zeta potential of the surface of the original alumina ceramic membrane was 2 mV, while the isoelectric point of the surface of the hydrophilic and superoleophobic ceramic membrane prepared in Example 1 decreased to -6 mV, and the negative charge on its membrane surface increased.

[0055] The above test results show that the hydrophilic and superoleophobic ceramic membrane prepared in Example 1 has very good hydrophilicity and underwater oleophobicity, which is significantly different from the original membrane, proving that the ceramic membrane prepared by the present invention has a complete iron oxide film layer and excellent performance.

[0056] Example 4

[0057] An oil-water separation experiment was carried out on the prepared 1000 ppm soybean oil-water emulsion using the original alumina ceramic membrane and the hydrophilic and superoleophobic ceramic membrane prepared in Example 1. During the membrane separation process, the transmembrane pressure difference was 1 bar, the membrane surface flow rate was 1 m / s, and the temperature was 20 °C. The membrane flux was detected during the membrane separation process. The experimental results are as Figure 7 shown. The results show that after the ceramic membrane operated for 60 min, the stable flux of the original alumina ceramic membrane was 193 L·m -2 ·h -1 , while the stable flux of the hydrophilic and superoleophobic ceramic membrane prepared in Example 1 was 493 L·m -2 ·h -1 , which was 155% higher than that of the original ceramic membrane, and the membrane flux increased significantly. In addition, after the oil-water separation was completed, the permeation flux of the hydrophilic and superoleophobic ceramic membrane prepared in Example 1 decreased by only about 10%, while the original ceramic membrane decreased by about 43%, indicating that the anti-pollution ability of the hydrophilic and superoleophobic ceramic membrane of the present invention was significantly enhanced.

[0058] After 60 minutes of the oil-water separation experiment, the membrane surface was rinsed with pure water for 30 minutes, and then the membrane flux was measured again. The membrane flux recovery rate was calculated. The experimental results are as Figure 8 shown. The results show that the membrane flux recovery rate of the original alumina ceramic membrane is 41%, while that of the hydrophilic and super-oleophobic ceramic membrane prepared in Example 1 increases to 71%, which is 30% higher than that of the original ceramic membrane. The membrane flux recovery performance is significantly improved.

[0059] Example 5

[0060] The hydrophilic and super-oleophobic ceramic membrane prepared in Example 1 (with a pore size of about 100 nm and a membrane area of 0.002 m 2 ) was applied to the oil-water separation process of the raw material liquid in the 9α-hydroxyandrostenedione extraction process. The process flow of the 9α-hydroxyandrostenedione extraction is as Figure 9 shown. After pretreating 18 kg of phytosterol fermentation broth (containing 1.8 kg of soybean oil and 14.91 kg of sterol), 4.5 kg of raw material liquid was obtained. The hydrophilic and super-oleophobic ceramic membrane prepared in Example 1 was used to separate the oil and water in the raw material liquid (the transmembrane pressure difference was 1 bar, the membrane surface flow rate was 1 m / s, and the temperature was 20 °C during the membrane separation process). 3.6 kg of oil-phase concentrate was collected. 7.2 kg of methanol was added to the oil-phase concentrate for extraction twice. After collecting the methanol extract, about 13.3 g of 9α-hydroxyandrostenedione was detected by ultraviolet light. After evaporation, concentration and decolorization, 14.2 g of crude 9α-hydroxyandrostenedione was obtained. The product yield was 89.2% and the purity was 93.7%.

[0061] Applying the hydrophilic and super-oleophobic ceramic membrane prepared in Example 1 to the oil-water separation process of the raw material liquid in the 9α-hydroxyandrostenedione extraction process greatly reduces the usage amount of the subsequent methanol extractant and the time of the extraction process, and reduces the operation energy consumption.

[0062] The present invention provides a hydrophilic and super-oleophobic ceramic membrane and its preparation ideas and methods. There are many specific methods and ways to implement this technical solution. The above description is only the preferred embodiment of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention. Each component not clearly defined in this embodiment can be realized by existing technologies.

Claims

1. A hydrophilic and superoleophobic ceramic membrane, characterized in that, A complete α-Fe2O3 film layer is formed on the surface of the microporous ceramic membrane; for the α-Fe2O3 film layer, its average pore diameter is 2 - 100 nm, porosity is 35 - 40%, and film thickness is 1 - 2 microns.

2. The hydrophilic and superoleophobic ceramic membrane according to claim 1, wherein The microporous ceramic membrane includes a support and a transition layer loaded on the surface of the support. For the support and the transition layer, their materials are independently selected from any one or several combinations of alumina, zirconia, magnesia, silica, titania, ceria, yttria, barium titanate, cordierite, mullite, forsterite, steatite, silicon aluminum oxynitride ceramics, zircon, ferrite, silicon nitride, aluminum nitride, silicon carbide, hydroxyapatite, carbon, silicon, clay, clay minerals, ceramic waste, silica sand, ceramic stone, feldspar, and white sand.

3. The hydrophilic and superoleophobic ceramic membrane according to claim 2, wherein For the transition layer, its average pore diameter is 0.1 - 1 μm.

4. The preparation method of the hydrophilic and super oleophobic ceramic membrane according to any one of claims 1 to 3, characterized in that, It includes the following steps: Step 1, an iron chloride aqueous solution undergoes a high-temperature hydrolysis reaction to obtain an iron hydroxide sol, which is cooled to 70 - 90 °C, and an aqueous solution of polyvinyl alcohol is added to the iron hydroxide sol to obtain an iron hydroxide sol film-forming solution; wherein, the polyvinyl alcohol is polyvinyl alcohol type 124; the content of polyvinyl alcohol in the iron hydroxide sol film-forming solution is 0.05 - 2.5 wt%, and the solid content of iron hydroxide is 0.1 - 0.6 wt%. Step 2, the microporous ceramic membrane is immersed in the iron hydroxide sol film-forming solution obtained in Step 1 for 1 - 60 s and then taken out, dried, and calcined to obtain the product.

5. The preparation method according to claim 4, characterized in that, In Step 1, the iron chloride is any one of anhydrous FeCl3, FeCl3·6H2O, 2FeCl3·7H2O, and 2FeCl3·5H2O; the high-temperature hydrolysis reaction is: the iron chloride aqueous solution is dropped into boiling water and reacted at a temperature of 90 - 100 °C for 0.1 - 12 h.

6. The preparation method according to claim 4, characterized in that, In Step 1, after adding the aqueous solution of polyvinyl alcohol to the iron hydroxide sol, it is reacted under stirring and at a temperature of 70 - 90 °C for 10 - 30 min to obtain the iron hydroxide sol film-forming solution.

7. The preparation method according to claim 4, wherein In Step 1, the particle size of the iron hydroxide colloid in the iron hydroxide sol film-forming solution is 100 - 200 nm.

8. The preparation method according to claim 4, characterized in that, In Step 2, the drying temperature is 25 - 110 °C, and the drying time is 1 - 48 h; the calcination temperature is 450 - 1000 °C, and the calcination time is 1 - 24 h.

9. Application of the hydrophilic and super-oleophobic ceramic membrane according to any one of claims 1 - 3 in the oil-water separation of an oil-water mixed system.

10. The application according to claim 9, wherein The oil-water mixed system is a mixed system of emulsified oil and water.

Citation Information

Patent Citations

  • Ferric oxide ultrafiltration plate ceramic membrane

    CN110075722A

  • Anti-pollution ceramic membrane as well as preparation method and application thereof

    CN113926321A